Investigation of the Effects of School Principals' Instructional Leadership Behaviors on Teachers' Self-Efficacy According to Teachers' Views - Kılınç, Alparslan; Ceylan, Hakan; Demir, Mesut; Emre, İrfan (Durmuş BURAK, 2023)
The aim of this study is to determine the relationship between school administrators' instructional leadership levels and teachers' self-efficacy perception levels according to teachers' views. 334 teachers working in primary and secondary schools participated in the research carried out with the correlational survey method. In this study, the MANOVA test was used to examine the views on the sub-dimensions of the scales according to the variables and Pearson correlation was used. Also multiple regression analysis was used to determine the level of the relationship. When the results obtained from the research were evaluated in terms of teachers' self-efficacy perceptions, it was seen that there was no significant difference between the groups in terms of gender and age variables. However, it was observed that there was a significant difference between the groups in terms of school type and seniority variables (p<.05). When the results of the research on the instructional leadership scale were examined, it was concluded that there was no significant difference between the groups in terms of seniority variable (p.>05), but there was a significant difference in sub-dimensions in terms of gender, school type and age variables. When the Pearson correlation results of this study were examined, it was concluded that there were relations at different levels in terms of various variables. The results of multiple linear regression analysis also showed that there is a significant relationship (R=.217; R2= .047) between instructional leadership sub-dimensions and teacher self-efficacy. It was concluded that three sub-dimensions explained 4.7% of teachers' self-efficacy.
Keywords: Studies on Education; Eğitim Üzerine Çalışmalar